2011
DOI: 10.1186/1756-9966-30-84
|View full text |Cite
|
Sign up to set email alerts
|

Absent Toll-like receptor-9 expression predicts poor prognosis in renal cell carcinoma

Abstract: BackgroundToll-like receptor 9 (TLR9) is a cellular DNA-receptor whose activation with cognate ligands triggers an immune reaction, with increased production of inflammatory cytokines. The aim of this study was to examine the expression of TLR9 in renal cell carcinoma (RCC), which is generally renowned of its immunogenic nature. We also evaluated the prognostic value of TLR9 in RCC.MethodsTLR9 expression in RCC was characterized with immunohistochemistry in a retrospective study population of 152 RCC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…TLR9 overexpression by cancer epithelial [35][36][37][38][39][40][41]. Results from our study are in agreement with those reported in the literature [42].…”
Section: Discussionsupporting
confidence: 83%
“…TLR9 overexpression by cancer epithelial [35][36][37][38][39][40][41]. Results from our study are in agreement with those reported in the literature [42].…”
Section: Discussionsupporting
confidence: 83%
“…The interaction of these motifs with the TLRs triggers a cascade of signaling events which stimulate the products of pro-inflammatory cytokines and chemokines to respond to the invading pathogen. As a member of the TLR family, TLR9 expression is noted in many malignancies, such as lung and cervical cancer and NPC (30)(31)(32)(33). TLR9 activation can induce high expression of cytokines and chemokines, cause tumorinflammatory microenvironment formation and promote the occurrence and development of malignancies (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…11 Of the RCC specimens previously analyzed for TLR9 expression (n D 152), 94 were evaluable in this study for tumor infiltrating CD8 C T lymphocytes. The reasons for the lack of complete cohort included loss of the tumor blocks or folding of the specimens during antigen retrieval and/or staining.…”
Section: Association Of Cd8 C T Cell Infiltration With Disease Stage mentioning
confidence: 99%
“…4,6 Although initially thought to be limited only to the innate immune system, it is now well established that TLR9 is widely expressed also in various cancer types, such as in breast, brain, gastric, lung, ovarian, prostate and kidney cancers as well as in cancers of the GI tract. [7][8][9][10][11][12][13][14][15][16][17] Stimulation of TLR9 expressing cancer cells with bacterial DNA-like, synthetic TLR9 ligands induces MMP-13-mediated invasion in vitro. 7,10,18,19 Based on these findings, it was expected that tumor TLR9 mediates invasion and metastasis and that high tumor TLR9 expression would be associated with worse survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation